Vectorial Drinfeld modular forms over Tate algebras - Pellarin, Federico; Perkins, Rudolph (International journal of number theory, 2018)
In this paper, we develop the theory of vectorial modular forms with values in Tate algebras introduced by the first author, in a very special case (dimension two, for a very particular representation of Γ:=GL2(Fq[θ])Γ:=GL2(𝔽q[𝜃])Γ<mspace width=".17em" class="thinspace"></mspace>:=<mspace width=".17em" class="thinspace"></mspace>GL2(𝔽q[𝜃])). Among several results that we prove here, we determine the complete structure of the modules of these forms, we describe their specializations at roots of unity and their connection with Drinfeld modular forms for congruence subgroups of ΓΓΓ and we prove that the modules generated by these forms are stable under the actions of Hecke operators.
Gesehen am 07.02.2020